Hubungan Pola Asuh Orang Tua Dengan Kejadian Stunting Pada Balita Diwilayah Kerja Puskesmas Tegalrejo Kota Yogyakarta - Zahara, Emi Laksmi; Ningsih, Sri Ratna (Universitas Respati Indonesia, 2025)
Background : Stunting is a condition where a baby is shorter than children of the same age. Stunting is a chronic nutritional problem that can affect a child's growth and development, and parenting plays an important role in determining a child's nutritional status. Objective : This study aims to determine the relationship between parenting patterns and the incidence of stunting in toddlers in the Tegalrejo Health Center work area, Yogyakarta City. Method : This study used a descriptive analytical design with a cross-sectional approach. A sample of 92 parents who have toddlers aged 1-5 years with a sampling method using accidental sampling and quota sampling. Data analysis to see the relationship between variables using the Spearman rank test. Results : Based on the results of the study, it showed that most respondents applied good parenting patterns (88%), while 12% were in the sufficient category. Of the 92 toddlers studied, 18 children experienced stunting, with 2 very short children (2.2%) and 16 short children (17.4%). There is a significant relationship between parenting patterns and stunting incidence, with a p-value of 0.000 (p